Water stress resistance of the new self-pollinated maize lines and hybrids - G. Ya. Krivosheev; N. А. Shevchenko (Зерновое хозяйство России)
The directions of the economic use of maize are different, namely fodder, food, technical. Considering that maize belongs to mesophytes, the most harmful stress factor for it is drought. The breeding maize for drought tolerance is considered the most important direction for this crop. The purpose of the current paper was to present study results of the drought resistance of the initial material, namely the self-pollinated maize lines and hybrids. The study was carried out at the Agricultural Research Center “Donskoy”, located in the zone of insufficient moisture in 2018–2020. Drought tolerance was determined by the method of residual water deficit (RWD). As an initial material, there were used 24 self-pollinated maize lines and 50 test-cross hybrids. There have been identified the new drought-resistant middle-early and middle-ripening self-pollinated lines ‘KS 317 A’,’ KV 240’, ‘LSh 16’, ‘S 86’, ‘LSh 17’ and ‘LSh 2’, ‘SP 246 / 276-2’, ‘DS 498 / 203-4’, ‘DS 298 / 203-3’, ‘DS 257 / 85-0’, ‘SP 280-3’, ‘KB 373’, which had a low residual water deficit in the flowering phase (7.7–10.4%) and did not significantly increase it during the period from vegetation to milky-wax ripeness (up to 10,3–12.6%). The drought-resistant hybrids include ‘Stepnyak MV’, ‘GK 26 AM × DS 257 / 85-0’, ‘P 101 × Zp 498 A’, ‘KB 399 × S 232’, ‘GK 26 AM × KB 373’, ‘GK 26 AM × SP 246 / 276-2’, ‘C 204 × KS 318’. They were characterized by a low water deficit during the flowering period (7.4–10.4%) and its low increase (1.4–3.7%) during the growing season. Drought-resistant hybrids, as a rule, included drought-resistant lines. According to the results of the State Variety Testing, the new middle-ripening three-line maize hybrid ‘Stepnyak MV’ ((KB 262 M × KB 326 ZM) × KB 498 MV)), developed on the basis of the drought-resistant lines ‘KB 262 M’ and ‘KB 498 MV’, has been included into the State Register since 2019. The hybrid possessed a high grain yield (4.55 t/ha) in the dry years of 2018–2020. it was characterized by high values of the main economically valuable traits, such as high resistance to lodging (0.5% of lodged plants), high starch content in grain (72.0%), optimum grain moisture (14.0%) by the harvesting time.